, 24.01.2020bigbear123

# Given: f(x) = 2x - 1; g(x) = 3x + 2; h(x) = x2 find f[g(x)] - f(x) kakkakak1320

Step-by-step explanation:

hello :

Given: F(x) = 2x - 1; G(x) = 3x + 2; H(x) = x2

Find F{G[H(2)]}

calculate : H(2) =2² =4

G[H(2)] =G= 3(4)+2 =14

F{G[H(2)]} = F{14}=2(14) =28 colebash88

6

Step-by-step explanation: 5

Step-by-step explanation:

The question ask for G[H(1)] so we have to find the H(1) first and it doesn't ask for anything about the F(x) so we don't have to worry about it. I dont know if H(x) = x*2 or x^2 but i'll consider it as x^2.

H(1) = (1)^2 Plug in 1 for x

H(1) = 1

since we find H(1) = 1 we just put it as G(1) because its same as G[H(1)]

G(1) = 3x + 2

G(1) = 3(1) +2 =5

G(1) = G[H(1)] = 5  ### Other questions on the subject: Mathematics Mathematics, 21.06.2019, laywah4
I’m pretty sure it’s 268 if I’m wrong I’m sorry...Read More Mathematics, 21.06.2019, tifftiff22
a’b’ = 6, cd = 10step-by-step explanation: the scale factor is 1/2. multiply 12 by 1/2 to get 6 for a’b’.to get cd, multiply 5 by 2 to get 10 for cd....Read More Mathematics, 21.06.2019, 2024daisjavien
answer:   the paragraph proof is mentioned below.step-by-step explanation: given: in a δxwy where $$z\in wy$$ such that, ∠wzx ≅ ∠yzx and zw≅zywe have to prove that:...Read More Mathematics, 21.06.2019, rosas8 Mathematics, 21.06.2019, makailaaa2
this is   a website that can solve any math problem or equation. it will save your life. (it saved   mine! lol) can i have brainliest ? : )step-by-step explanation:...Read More $$x \times 6 = 108$$...Read More  